An N-polar AlGaN-GaN heterojunction epitaxial structure and its preparation method and application

By using Materials Studio for model construction and thermodynamic stability calculation on the SiC substrate, combined with MOCVD technology to epitaxially grow the N-polar conversion layer, GaN functional layer and AlGaN functional layer, we solved the problem of N-polar AlGaN/GaN materials in the existing technology. The problem of poor growth quality has been solved, and high-quality, controllable growth of heterojunction epitaxial structures has been achieved.

CN117410179BActive Publication Date: 2025-01-24SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311258622.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-01-24
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

The prior art is difficult to grow high-quality, uniform N-polar AlGaN/GaN materials, especially on Si substrates, and the lattice mismatch between the substrate and the polar surface conversion layer is high, and additional buffering is required. layer, increasing process complexity and leading to poor material quality.

Method used

The Materials Studio program is used for model construction and thermodynamic stability calculation to determine suitable doping elements and concentrations. The N polarity conversion layer, GaN functional layer and AlGaN are sequentially epitaxially grown on the SiC substrate through metal organic chemical vapor deposition (MOCVD). Functional layer avoids the introduction of buffer layer.

Benefits of technology

The controllable growth of high-quality N-polar AlGaN-GaN heterojunction epitaxial structures is achieved, simplifying the process, reducing costs, and improving the thermal conductivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117410179B_ABST
    Figure CN117410179B_ABST
Patent Text Reader

Abstract

The present invention discloses an N-polarity AlGaN-GaN heterojunction epitaxial structure, a preparation method and application thereof. The preparation method of the N-polarity AlGaN-GaN heterojunction epitaxial structure of the present invention comprises the following steps: 1) determining the type of doping elements in the N-polarity conversion layer; 2) determining the concentration of doping elements in the N-polarity conversion layer; 3) annealing the SiC substrate using an annealing furnace; 4) epitaxially growing the N-polarity conversion layer, the GaN functional layer and the AlGaN functional layer on the SiC substrate in sequence using metal organic chemical vapor deposition. The present invention introduces a first-principles calculation method, and realizes the controllable growth of the N-polarity AlGaN-GaN heterojunction by introducing a polarity conversion layer between the SiC substrate and the functional layer. Finally, a high-quality N-polarity AlGaN-GaN heterojunction epitaxial structure can be prepared by a simple and efficient method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor devices, and in particular to an N-polar AlGaN-GaN heterojunction epitaxial structure and a preparation method and application thereof. Background Art

[0002] AlGaN materials have the characteristics of high electron mobility, good thermal stability, and good chemical stability. Moreover, by adjusting the Al content, the bandgap width can be continuously adjusted from 3.4eV to 6.2eV. In addition, AlGaN can be combined with GaN to form an AlGaN / GaN heterojunction, thereby improving the performance of the material. N-polar AlGaN / GaN heterojunction materials have low contact resistance and can effectively suppress the short channel effect. They have been widely used in the field of rectifier devices. However, the current method of growing AlGaN / GaN materials on the N-polar surface using Si substrates is difficult to grow high-quality and uniform GaN functional layers, and the lattice mismatch between the substrate and the polar surface conversion layer is high, requiring the introduction of an additional buffer layer, which increases the complexity of the process and leads to poor quality of the grown material, making it difficult to meet the growing requirements of practical applications.

[0003] Therefore, it is of great significance to develop a simple and efficient method for preparing N-polar AlGaN-GaN heterojunction epitaxial structure and to prepare high-quality N-polar AlGaN-GaN heterojunction epitaxial structure. Summary of the invention

[0004] The object of the present invention is to provide an N-polar AlGaN-GaN heterojunction epitaxial structure and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is:

[0006] A method for preparing an N-polar AlGaN-GaN heterojunction epitaxial structure comprises the following steps:

[0007] 1) The Materials Studio program is used to construct the N-polar conversion layer doping element model, and then the CASTEP module in the Materials Studio program package is used to perform structural optimization and thermodynamic stability calculation of the model to determine the most thermodynamically stable doping element;

[0008] 2) Using Materials Studio program to construct the atomic adsorption model of the N-polar conversion layer, and then using the CASTEP module in the Materials Studio program package to perform structural optimization and thermodynamic stability calculations on the model to determine the doping concentration suitable for N-polar surface growth;

[0009] 3) Annealing the SiC substrate in an annealing furnace;

[0010] 4) According to the calculation results of step 1) and step 2), an N-polar conversion layer, a GaN functional layer and an AlGaN functional layer are sequentially epitaxially grown on a SiC substrate by metal organic chemical vapor deposition (MOCVD) to obtain an N-polar AlGaN-GaN heterojunction epitaxial structure.

[0011] Preferably, the doping element in the N-polarity conversion layer doping element model in step 1) is one of Be, Mg and Ca, and the doping concentration is 50%.

[0012] Preferably, the doping concentration of the doping element in the N-polarity conversion layer atomic adsorption model in step 2) is 2% to 10%.

[0013] Preferably, the hybrid functional used in the thermodynamic stability calculation in step 1) and step 2) is GGA+PBE, the cutoff energy is 450 eV, the K-point grid is set to 3×3×1, and the energy convergence standard is set to 1.0×10 -5 eV / atom.

[0014] Preferably, in step 3), the thickness of the SiC substrate is 850 μm to 860 μm.

[0015] Preferably, the annealing in step 3) is performed in an argon atmosphere at a temperature of 650° C. to 750° C. for 20 to 30 minutes. Annealing can remove impurities such as oxides on the surface of the SiC substrate, which is conducive to better meeting the controllable growth requirements of the N-polar AlGaN-GaN heterojunction epitaxial structure.

[0016] Preferably, in step 4), the N-polarity conversion layer is a Mg-doped GaN layer, and the Mg doping concentration is 2E19 / cm 3 ~1E20 / cm 3 .

[0017] Preferably, in step 4), the thickness of the N-polarity conversion layer is 1.0 μm to 2.0 μm.

[0018] Preferably, in step 4), the growth temperature of the N-polarity conversion layer is 900°C to 1050°C.

[0019] Preferably, in step 4), the thickness of the GaN functional layer is 150 nm to 250 nm.

[0020] Preferably, the growth temperature of the GaN functional layer in step 4) is 950°C to 1100°C.

[0021] Preferably, in step 4), the thickness of the AlGaN functional layer is 100 nm to 200 nm.

[0022] Preferably, in step 4), the growth temperature of the AlGaN functional layer is 850°C to 1050°C.

[0023] An N-polar AlGaN-GaN heterojunction epitaxial structure is manufactured by the above-mentioned manufacturing method.

[0024] A high electron mobility transistor comprises the above-mentioned N-polarity AlGaN-GaN heterojunction epitaxial structure.

[0025] The design concept of the N-polar AlGaN-GaN heterojunction epitaxial structure of the present invention is as follows:

[0026] 1) Designed N-polar conversion layer doping element model: A doping concentration of 50% was selected for screening doping elements, which not only effectively reduced the amount of calculation of the model, but also increased the differentiation of thermodynamic stability between different doping elements. Finally, Mg was determined as the doping element;

[0027] 2) Designed N-polar conversion layer atomic adsorption model: For model structures with high atomic weight, the use of GGA+PBE hybrid functional can effectively reduce the computational cost and obtain simulation results with guiding significance;

[0028] 3) The designed doping model is an equal-step long-gradient doping model: Since the carrier excitation concentration of intrinsic GaN material is extremely low, the default value is 10 5 One GaN atom is excited, and according to the intrinsic carrier concentration of GaN, 16 / cm 3 It is known that the atomic concentration in GaN is about 10 21 / cm 3 , so the Mg doping concentration of 2% to 10% corresponds to 2E19 / cm 3 ~1E20 / cm 3 By comparing the thermodynamic stability under different doping concentrations, the most stable Mg doping concentration is determined to guide the epitaxial growth of high-quality N-polar AlGaN / GaN materials;

[0029] 4) Design of N-polar AlGaN-GaN heterojunction epitaxial structure on SiC substrate: In order to solve the lattice mismatch and thermal mismatch problems between GaN material and SiC substrate, high-quality GaN layer is directly epitaxially grown, avoiding the introduction of buffer layer and reducing the preparation cost.

[0030] The beneficial effects of the present invention are as follows: the present invention introduces a first-principles calculation method, and realizes the controllable growth of an N-polar AlGaN-GaN heterojunction by introducing a polarity conversion layer between a SiC substrate and a functional layer, and finally a high-quality N-polar AlGaN-GaN heterojunction epitaxial structure can be prepared by a simple and efficient method.

[0031] Specifically:

[0032] 1) The present invention provides a first-principles simulation method, which provides a leading role by exploring the method of thermodynamic stability (for example, by screening out the most thermodynamically stable doping element in the N-polar conversion layer and determining the doping concentration that is most likely to form N-polar surface GaN molecule adsorption in the N-polar conversion layer molecular adsorption model through simulation research, effectively guiding the growth of high-quality AlGaN-GaN heterojunction epitaxial structure), reducing the trial and error cost in actual experiments and improving the efficiency of material growth;

[0033] 2) The present invention uses an annealing furnace to perform surface pretreatment of the SiC substrate, which effectively reduces the process complexity and cost of the surface treatment and is conducive to large-scale production;

[0034] 3) The present invention improves the quality of the AlGaN-GaN heterojunction epitaxial structure by introducing a SiC substrate, avoids the introduction of a buffer layer, increases the thermal conductivity of the material, and simplifies the process;

[0035] 4) The present invention adopts the MOCVD high-temperature epitaxial method to successively grow an N-polarity conversion layer, a GaN functional layer and an AlGaN functional layer on a SiC substrate. The preparation method has the advantages of high process continuity, time-saving and high efficiency, low energy consumption, etc., and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of a partial interface model of the N-polarity conversion layer doping element model in the present invention.

[0037] Figure 2 It is a schematic diagram of a part of the interface model of the N-polar conversion layer atomic adsorption model in the present invention.

[0038] Figure 3 This is a comparison diagram of the binding energies of the N-polarity conversion layer doping element models of different doping elements in Example 1.

[0039] Figure 4 3 is a comparison diagram of the binding energy of the atomic adsorption model of the N-polar conversion layer with different doping concentrations in Example 1.

[0040] Figure 5 It is a schematic diagram of the cross-sectional structure of the N-polar AlGaN-GaN heterojunction epitaxial structure of the present invention. DETAILED DESCRIPTION

[0041] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0042] The N-polarity conversion layer doping element model in Examples 1 to 4 (partial interface model schematic diagram as shown in FIG. Figure 1 As shown in the figure, it contains two GaN molecules, one Ga atom, two N atoms, and one doping atom, where the N atom is on top and the Ga atom on top is replaced by the doping atom. The vacuum layer thickness is

[0043] The atomic adsorption model of the N-polar conversion layer in Examples 1 to 4 (partial interface model schematic diagram as shown in FIG. Figure 2 As shown in the figure, a is N polar surface adsorption, b is Ga polar surface adsorption) contains 50 N atoms, 45-49 Ga atoms, 1-5 Mg atoms, where Mg atoms randomly replace Ga atoms, the adsorbed molecule is GaN, divided into N side up and Ga side up, where the atoms on the contact surface are perpendicular to each other, and the vertical distance is The vacuum layer thickness is

[0044] The thickness of the SiC substrate in the N-polar AlGaN-GaN heterojunction epitaxial structure of Examples 1 to 4 is 850 μm to 860 μm, the thickness of the N-polar conversion layer is 1.0 μm to 2.0 μm, and the doping concentration is 4E19 / cm 3 ~8E19 / cm 3 , the thickness of the GaN functional layer is 150nm~250nm, and the thickness of the AlGaN functional layer is 100nm~200nm.

[0045] The length and width dimensions of the SiC substrate layer, the N-polarity conversion layer, the GaN functional layer and the AlGaN functional layer in the N-polarity AlGaN-GaN heterojunction epitaxial structures of Examples 1 to 4 and Comparative Examples 1 to 2 are all 5 cm×5 cm.

[0046] Embodiment 1:

[0047] An N-polar AlGaN-GaN heterojunction epitaxial structure, the preparation method of which is as follows:

[0048] 1) Use Materials Studio program to build the N-polar conversion layer doping element model (build the vacuum layer thickness 1×1×2 unit cell structure, with N, X, N and Ga atoms from top to bottom, where X is one of Be, Mg and Ca), and then the CASTEP module in the Materials Studio package was used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm used the GGA+PBE algorithm; the cutoff energy was selected to be 450 eV, the K-point grid was set to 3×3×1, and the energy convergence standard was set to 1.0×10 -5 eV / atom; The binding energy comparison diagram of the N-polar conversion layer doping element model with different doping elements is shown in Figure 3 The most thermodynamically stable doping element was determined, and the doping element finally determined was Mg;

[0049] 2) Use Materials Studio program to build the N-polar conversion layer atomic adsorption model (build the vacuum layer thickness 5×5×2 periodic supercell structure, and a point is selected on the top for molecular adsorption, the distance between the two is The upper part is the GaN molecule, which is divided into two situations: Ga-side up and N-side up. The lower part is the N polarity conversion layer, which contains 50 N atoms, x Mg atoms and (50-x) Ga atoms, where x changes from 1 to 5 in sequence, and Mg atoms randomly replace Ga sites). The CASTEP module in the Materials Studio package is used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm uses the GGA+PBE algorithm; the cutoff energy is selected as 450 eV, the K point grid is set to 3×3×1, and the energy convergence standard is set to 1.0×10 -5 eV / atom; The binding energy comparison diagram of the atomic adsorption model of the N-polar conversion layer with different doping concentrations is shown in Figure 4 The doping concentration suitable for N-polar surface growth is determined as shown in Figure 2. The final Mg doping concentration is 4E19 / cm 3 ;

[0050] 3) placing the SiC substrate in an annealing furnace and annealing it for 20 min at 650°C in an argon atmosphere;

[0051] 4) Based on the calculation results of step 1) and step 2), a 1.0 μm thick N-polar conversion layer (Mg-doped GaN), a 150 nm thick GaN functional layer, and a 100 nm thick AlGaN functional layer are sequentially epitaxially grown on a SiC substrate using metal organic chemical vapor deposition, and the growth temperatures are 900° C., 950° C., and 850° C., respectively, to obtain an N-polar AlGaN-GaN heterojunction epitaxial structure (the cross-sectional structure schematic diagram is shown in FIG. 4 ). Figure 5 shown).

[0052] Comparative Example 1:

[0053] An N-polar AlGaN-GaN heterojunction epitaxial structure, the preparation method of which is as follows:

[0054] 1) Place the SiC substrate in an annealing furnace and anneal it for 50 minutes in an argon atmosphere at a temperature of 1000°C;

[0055] 2) A 4 μm thick N-polarity conversion layer (Mg-doped GaN), a 530 nm thick GaN functional layer, and a 580 nm thick AlGaN functional layer were epitaxially grown on a SiC substrate using metal organic chemical vapor deposition. The growth temperatures were 800°C, 830°C, and 730°C, respectively. The Mg doping concentration of the N-polarity conversion layer was 8E20 / cm 3 , and an N-polar AlGaN-GaN heterojunction epitaxial structure is obtained.

[0056] Performance Testing:

[0057] After testing (X-ray rocking curve test and reflection high-energy electron diffraction test of the

[001] plane of the AlGaN functional layer), the crystal quality and crystal orientation of the N-polar AlGaN-GaN heterojunction epitaxial structure of Example 1 are significantly better than those of the N-polar AlGaN-GaN heterojunction epitaxial structure of Comparative Example 1.

[0058] Embodiment 2:

[0059] An N-polar AlGaN-GaN heterojunction epitaxial structure, the preparation method of which is as follows:

[0060] 1) Use Materials Studio program to build the N-polar conversion layer doping element model (build the vacuum layer thickness 1×1×2 unit cell structure, with N, X, N and Ga atoms from top to bottom, where X is one of Be, Mg and Ca), and then the CASTEP module in the Materials Studio package was used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm used the GGA+PBE algorithm; the cutoff energy was selected to be 450 eV, the K-point grid was set to 3×3×1, and the energy convergence standard was set to 1.0×10 -5 eV / atom) to determine the most thermodynamically stable doping element, and the final doping element was Mg;

[0061] 2) Use Materials Studio program to build the N-polar conversion layer atomic adsorption model (build the vacuum layer thickness 5×5×2 periodic supercell structure, and a point is selected on the top for molecular adsorption, the distance between the two is The upper part is the GaN molecule, which is divided into two situations: Ga-side up and N-side up. The lower part is the N polarity conversion layer, which contains 50 N atoms, x Mg atoms and (50-x) Ga atoms, where x changes from 1 to 5 in sequence, and Mg atoms randomly replace Ga sites). The CASTEP module in the Materials Studio package is used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm uses the GGA+PBE algorithm; the cutoff energy is selected as 450 eV, the K point grid is set to 3×3×1, and the energy convergence standard is set to 1.0×10 -5 eV / atom) to determine the doping concentration suitable for N-polar surface growth, and the final Mg doping concentration was 5E19 / cm 3 ;

[0062] 3) placing the SiC substrate in an annealing furnace and annealing it for 22 minutes at 670°C in an argon atmosphere;

[0063] 4) Based on the calculation results of step 1) and step 2), a 1.2 μm thick N-polarity conversion layer (Mg-doped GaN), a 170 nm thick GaN functional layer, and a 120 nm thick AlGaN functional layer are sequentially epitaxially grown on a SiC substrate using metal organic chemical vapor deposition. The growth temperatures are 920° C., 970° C., and 870° C., respectively, to obtain an N-polarity AlGaN-GaN heterojunction epitaxial structure (the cross-sectional structure schematic diagram is shown in FIG. 4 ). Figure 5 shown).

[0064] Comparative Example 2:

[0065] An N-polar AlGaN-GaN heterojunction epitaxial structure, the preparation method of which is as follows:

[0066] 1) Place the SiC substrate in an annealing furnace and anneal it for 55 minutes at 1020°C in an argon atmosphere;

[0067] 2) A 5 μm thick N-polarity conversion layer (Mg-doped GaN), a 560 nm thick GaN functional layer, and a 610 nm thick AlGaN functional layer were epitaxially grown on a SiC substrate using metal organic chemical vapor deposition. The growth temperatures were 830°C, 860°C, and 760°C, respectively. The Mg doping concentration of the N-polarity conversion layer was 5E20 / cm 3 , and an N-polar AlGaN-GaN heterojunction epitaxial structure is obtained.

[0068] Performance Testing:

[0069] After testing (X-ray rocking curve test and reflection high-energy electron diffraction test of the

[001] plane of the AlGaN functional layer), the crystal quality and crystal orientation of the N-polar AlGaN-GaN heterojunction epitaxial structure of Example 2 are significantly better than those of the N-polar AlGaN-GaN heterojunction epitaxial structure of Comparative Example 2.

[0070] Embodiment 3:

[0071] An N-polar AlGaN-GaN heterojunction epitaxial structure, the preparation method of which is as follows:

[0072] 1) Use Materials Studio program to build the N-polar conversion layer doping element model (build the vacuum layer thickness 1×1×2 unit cell structure, with N, X, N and Ga atoms from top to bottom, where X is one of Be, Mg and Ca), and then the CASTEP module in the Materials Studio package was used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm used the GGA+PBE algorithm; the cutoff energy was selected to be 450 eV, the K-point grid was set to 3×3×1, and the energy convergence standard was set to 1.0×10 -5 eV / atom) to determine the most thermodynamically stable doping element, and the final doping element was Mg;

[0073] 2) Use Materials Studio program to build the N-polar conversion layer atomic adsorption model (build the vacuum layer thickness 5×5×2 periodic supercell structure, and a point is selected on the top for molecular adsorption, the distance between the two is The upper part is the GaN molecule, which is divided into two situations: Ga-side up and N-side up. The lower part is the N polarity conversion layer, which contains 50 N atoms, x Mg atoms and (50-x) Ga atoms, where x changes from 1 to 5 in sequence, and Mg atoms randomly replace Ga sites). The CASTEP module in the Materials Studio package is used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm uses the GGA+PBE algorithm; the cutoff energy is selected as 450 eV, the K point grid is set to 3×3×1, and the energy convergence standard is set to 1.0×10 -5 eV / atom) to determine the doping concentration suitable for N-polar surface growth, and the final Mg doping concentration was 6E19 / cm 3 ;

[0074] 3) placing the SiC substrate in an annealing furnace and annealing it for 25 min in an argon atmosphere at a temperature of 690°C;

[0075] 4) Based on the calculation results of step 1) and step 2), a 1.5 μm thick N-polar conversion layer (Mg-doped GaN), a 200 nm thick GaN functional layer, and a 150 nm thick AlGaN functional layer are sequentially epitaxially grown on a SiC substrate using metal organic chemical vapor deposition. The growth temperatures are 950° C., 1000° C., and 900° C., respectively, to obtain an N-polar AlGaN-GaN heterojunction epitaxial structure (the cross-sectional structure schematic diagram is shown in FIG. 4 ). Figure 5 shown).

[0076] After testing (the testing method is the same as that of Example 1), it is found that the crystal quality and crystal orientation of the N-polar AlGaN-GaN heterojunction epitaxial structure of this embodiment are very good.

[0077] Embodiment 4:

[0078] An N-polar AlGaN-GaN heterojunction epitaxial structure, the preparation method of which is as follows:

[0079] 1) Use Materials Studio program to build the N-polar conversion layer doping element model (build the vacuum layer thickness 1×1×2 unit cell structure, with N, X, N and Ga atoms from top to bottom, where X is one of Be, Mg and Ca), and then the CASTEP module in the Materials Studio package was used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm used the GGA+PBE algorithm; the cutoff energy was selected to be 450 eV, the K-point grid was set to 3×3×1, and the energy convergence standard was set to 1.0×10 -5 eV / atom) to determine the most thermodynamically stable doping element, and the final doping element was Mg;

[0080] 2) Use Materials Studio program to build the N-polar conversion layer atomic adsorption model (build the vacuum layer thickness 5×5×2 periodic supercell structure, and a point is selected on the top for molecular adsorption, the distance between the two is The upper part is the GaN molecule, which is divided into two situations: Ga-side up and N-side up. The lower part is the N polarity conversion layer, which contains 50 N atoms, x Mg atoms and (50-x) Ga atoms, where x changes from 1 to 5 in sequence, and Mg atoms randomly replace Ga sites). The CASTEP module in the Materials Studio package is used to perform structural optimization and thermodynamic stability calculations of the model (the minimization algorithm uses the GGA+PBE algorithm; the cutoff energy is selected as 450 eV, the K point grid is set to 3×3×1, and the energy convergence standard is set to 1.0×10 -5eV / atom) to determine the doping concentration suitable for N-polar surface growth, and the final Mg doping concentration was 8E19 / cm 3 ;

[0081] 3) placing the SiC substrate in an annealing furnace and annealing it for 28 minutes at 730°C in an argon atmosphere;

[0082] 4) Based on the calculation results of step 1) and step 2), a 1.8 μm thick N-polar conversion layer (Mg-doped GaN), a 230 nm thick GaN functional layer, and a 180 nm thick AlGaN functional layer are sequentially epitaxially grown on a SiC substrate using metal organic chemical vapor deposition, and the growth temperatures are 980° C., 1030° C., and 930° C., respectively, to obtain an N-polar AlGaN-GaN heterojunction epitaxial structure (the cross-sectional structure schematic diagram is shown in FIG. 4 ). Figure 5 shown).

[0083] After testing (the testing method is the same as that of Example 1), it is found that the crystal quality and crystal orientation of the N-polar AlGaN-GaN heterojunction epitaxial structure of this embodiment are very good.

[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an N-polar AlGaN-GaN heterojunction epitaxial structure, characterized in that: The following steps are involved: 1) The Materials Studio program was used to construct the N-polar conversion layer doping element model, and then the CASTEP module in the Materials Studio program package was used to perform structural optimization and thermodynamic stability calculations on the model to determine the most thermodynamically stable doping element; 2) Use the Materials Studio program to build an atomic adsorption model of the N-polar conversion layer, and then use the CASTEP module in the Materials Studio program package to perform structural optimization and thermodynamic stability calculations on the model to determine the doping concentration suitable for N-polar surface growth; 3) Annealing the SiC substrate in an annealing furnace; 4) According to the calculation results of step 1) and step 2), an N-polar conversion layer, a GaN functional layer and an AlGaN functional layer are sequentially epitaxially grown on a SiC substrate by metal organic chemical vapor deposition, so as to obtain an N-polar AlGaN-GaN heterojunction epitaxial structure; Step 1) the doping element in the N-polarity conversion layer doping element model is one of Be, Mg, and Ca, and the doping concentration is 50%; Step 2) the doping concentration of the doping element in the N-polar conversion layer atomic adsorption model is 2% to 10%; The hybrid functional used in the thermodynamic stability calculations in step 1) and step 2) is GGA+PBE, the cutoff energy is 450 eV, the K-point grid is set to 3×3×1, and the energy convergence standard is set to 1.0×10 -5 eV / atom.

2. The preparation method according to claim 1, characterized in that: Step 3) The thickness of the SiC substrate is 850 μm to 860 μm.

3. The preparation method according to claim 1 or 2, characterized in that: Step 3) The annealing is performed in an argon atmosphere at a temperature of 650° C. to 750° C. for 20 min to 30 min.

4. The preparation method according to claim 1, characterized in that: Step 4) The thickness of the N-polarity conversion layer is 1.0 μm to 2.0 μm; Step 4) The thickness of the GaN functional layer is 150 nm to 250 nm; Step 4) The thickness of the AlGaN functional layer is 100 nm to 200 nm.

5. The preparation method according to claim 1 or 4, characterized in that: In step 4), the growth temperature of the N polarity conversion layer is 900°C to 1050°C; in step 4), the growth temperature of the GaN functional layer is 950°C to 1100°C; in step 4), the growth temperature of the AlGaN functional layer is 850°C to 1050°C.

Citation Information

Patent Citations

  • N-polarity AlGaN / GaN HEMT device and growth method thereof

    CN112687738A

  • Simulation method of InGaN doping performance

    CN113919143A